2015
DOI: 10.1007/s10072-015-2238-6
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell-based therapies for intracerebral hemorrhage in animal model: a meta-analysis

Abstract: Stem cell to be a new intervention for treating intracerebral hemorrhage (ICH) might benefit humans. Therefore, we collected animal studies to find the effect of this innovative treatment. In July 2014, we searched Medline (from 1950), Embase (from 1980), China Biology Medicine disk (from 1978) for studies on stem cells used for treating experimental ICH in animal models that reported neurobehavioral and structural outcome. We evaluated the quality of these studies and used a weighted mean difference random af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…At present, plenty of experimental research has been conducted on the treatment of rodent ICH with MSC transplantation, probably due to the versatility of rodent models. Large amounts of evidence confirmed that MSC transplantation is a promising treatment for neuronal recovery after ICH (Ma et al, 2015;Hu et al, 2016;Zheng et al, 2018). In view of the neurological function improvement effect of MSCs in ischemic rat brain, it was no doubt that the first MSC application in the rat ICH model also showed significant improvement in motor function (Zhang et al, 2006).…”
Section: Msc Transplantation In Rodentsmentioning
confidence: 99%
“…At present, plenty of experimental research has been conducted on the treatment of rodent ICH with MSC transplantation, probably due to the versatility of rodent models. Large amounts of evidence confirmed that MSC transplantation is a promising treatment for neuronal recovery after ICH (Ma et al, 2015;Hu et al, 2016;Zheng et al, 2018). In view of the neurological function improvement effect of MSCs in ischemic rat brain, it was no doubt that the first MSC application in the rat ICH model also showed significant improvement in motor function (Zhang et al, 2006).…”
Section: Msc Transplantation In Rodentsmentioning
confidence: 99%
“…Two recent meta-analyses concluded that the quality of original articles investigating the efficacy of stem cell therapies in animal models of ICH is still low [ 12 , 13 ], as assessed by the Collaborative Approach to Meta-Analysis and Review of Animal Data from Experimental Stroke (CAMARADES) checklist [ 65 ]. For instance, studies using animals with relevant comorbidities (aged, hypertensive, or diabetic) are still rare.…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…Other important parameters that are usually neglected or not informed by the authors are the control of body temperature during the surgeries, allocation concealment, blinded assessment of outcome, and sample size calculation [ 12 , 13 ]. In an elegant review, MacLellan and colleagues [ 66 ] identified and discussed some of the limitations of the current preclinical research on ICH.…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…Ma et al reviewing studies up to 2014, and demonstrated the beneficial effects of stem cell therapy in animal models of ICH. However, they did not perform various stratified analyses except cell type [ 27 ]. Hu et al reviewed studies up to 2015, provided key insights and focused on ICH, but they did not include the outcome “brain water content” as a structural indicator [ 16 ].…”
Section: Discussionmentioning
confidence: 99%